TWO-TIER MULTIPLE CHOICE (TTMC) INSTRUMENT FOR MEASURING STUDENTS' COMPLETE ABILITY QUESTION EVALUATED LEVEL (C5) - Eva Nauli Taib; Ika Fazira; Cut Ratna Dewi; Evinopita Taib (Universitas Islam Negeri Ar-Raniry, 2023)
Data from the Program For International Student Assessment (PISA) explains that the weakness of Indonesian students is their inability when faced with problems that require skills, are critical, and creative. This study aims to describe students' ability to solve C5 questions, which is a cognitive level in solving HOTS (High Order Thinking Skills) questions using the Two-Tier Multiple Choice instrument. This type of research uses a quantitative approach with a descriptive method. The results showed that the answer categories of students who understood an average of 4.2%, students who misconceived an average of 13%, students who guessed an average of 26% and students who did not understand had an average of 56%, this figure shows that the average The highest average of students did not understand or could not solve well the questions with the cognitive level of evaluating or C5, so that it became a source of assessment for understanding student learning concepts, and could foster motivation in learning.